ORGANIZATIONAL SUPPORT AND HEALTH INFRASTRUCTURE IMPACT ON HEALTHCARE STAFF RETENTION IN HINTERLAND COMMUNITIES - Mohammad Arief El Habibie; Etty Sri Wahyuni (RADJA PUBLIKA, 2025)
Healthcare workforce shortages in hinterland areas represent a critical global health challenge, particularly affecting remote communities that struggle to attract and retain qualified healthcare professionals. This cross-sectional study analyzed the influence of organizational support and health infrastructure on healthcare staff retention among 182 healthcare workers in hinterland communities of Riau Islands, Indonesia, using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The measurement model demonstrated excellent reliability and validity with Cronbach's Alpha values ranging from 0.924-0.947 and Average Variance Extracted above 0.5 for all constructs. Results revealed that health infrastructure had the strongest direct positive effect on staff retention, followed by organizational support, while health infrastructure also significantly influenced organizational support, creating a mediation pathway. The indirect effect analysis confirmed that organizational support partially mediates the relationship between health infrastructure and staff retention, with all hypothesized relationships being statistically significant and the model explaining substantial variance in retention outcomes. These findings suggest that healthcare organizations in hinterland areas should adopt integrated strategies that simultaneously invest in infrastructure improvements and strengthen organizational support systems to achieve optimal staff retention outcomes in challenging remote environments.